Agribusiness Indicators : Mozambique - World Bank (World Bank, Washington, DC, 2017)
Mozambique, the only Lusophone country covered in the agribusiness indicators initiative, has had a turbulent history since independence. Civil unrest over some 20 years and frequent drought in southern Mozambique, coupled with floods near the many waterways that transect the country (mainly east-west), have inhibited an agricultural transformation. Even so, Mozambique could be a regional breadbasket. The country has much potentially usable arable land, along with access to river water for irrigation in many agricultural production zones, particularly in central and northern Mozambique. Sesame, pigeon peas, and cashew exports are significant and rising, not to mention exports of industrial crops such as cotton, leaf tobacco, and sugarcane, yet production of grain and most other food crops remains stagnant. Irrigated area is way below what is possible and needed to increase yields and total agricultural output.